Note—A Dynamic Programming Algorithm for Joint Replenishment Under General Order Cost Functions - Rosenblatt, Meir J.; Kaspi, Moshe (Management Science, 1985)
The multi-item joint replenishment problem is generalized to allow ordering costs to be dependent on the specific items jointly supplied. A fixed cycle approach is examined in which all the items of a group are always jointly replenished. A dynamic programming algorithm is developed for partitioning the items into groups, each with its own fixed cycle time, resulting in an optimal fixed cycle replenishment policy.